The state of patient-centered care and associated factors at a large referral hospital in Northwestern Uganda: Perceptions of patients - Mary Aleni; Edson Mwebesa; Deus Twesigye; Monicah Andru; Mildred Edna Assusi; Irene Atuhairwe; Allan G. Nsubuga; Helen Ewing; Abbey Roepke (Elsevier, 2024)
Background: A Patient-Centered Care (PCC) approach to health service delivery is considered one of the essential domains of healthcare quality. This has been shown to improve patient satisfaction with health services and patient outcomes, but it has not been fully embraced in many low and middle income countries. Purpose: To evaluate patients' perceptions of PCC and identify the factors influencing perceived PCC at a large referral hospital in Northwestern Uganda. Materials and Methods: We conducted a descriptive cross-sectional correlational study. Four hundred and eighty (480) patients or their attendants participated in the study. Data was collected using an interviewer administered questionnaire. Statistical analysis was applied at univariate, bivariate and multivariate levels using Stata V.14 to assess the state of PCC, patient perceptions and factors associated with perceived PCC. Results: Sixty five percent (64.8 %) of the participants perceived they received PCC. Most of the dimensions of PCC were rated high on a 5-point Likert scale, with respect for patient's values and preferences ranked highest; mean score of 3.9 (SD = 0.9) and coordination of care ranked lowest, mean score of 3.5 (SD = 0.9). Being outpatient, single or never in union had a reduced perception score of PCC. Patients who had heard of PCC had a higher perception of PCC. Conclusion: Patient-Centered Care was rated optimally at ARRH. All the PCC dimensions were rated highly except coordination of care and information, education and communication which could be improved by building the capacity of health workers in effective communication and coordination of health care services.